Efficacy of SDHI fungicides, including benzovindiflupyr, against Colletotrichum species. Issue 10 (9th February 2016) - Ishii, Hideo; Zhen, Fan; Hu, Mengjun; Li, Xingpeng; Schnabel, Guido
Abstract: BACKGROUND: Colletotrichum species cause anthracnose diseases on many plants and crops. A new generation of succinate dehydrogenase inhibitors (SDHIs) was developed recently. The inhibitory activity of the five SDHI fungicides against Colletotrichum species was determined in this study. RESULTS: Isolates of C. gloeosporioides, C. acutatum, C. cereale and C. orbiculare were insensitive (naturally resistant) to boscalid, fluxapyroxad and fluopyram on YBA agar medium. In contrast, these isolates were relatively sensitive to penthiopyrad, except for C. orbiculare . Most interestingly, benzovindiflupyr showed highest inhibitory activity against all of these four species. Benzovindiflupyr was effective against C. gloeosporioides and C. acutatum on apple and peach fruit, as well as on cucumber plants inoculated with C. orbiculare . The sdhB, sdhC and sdhD genes encoding the subunits of fungicide‐targeted succinate dehydrogenase were sequenced, but, despite high polymorphisms, no apparent resistance mutations were found in Colletotrichum species. CONCLUSIONS: This is the first report on the activity of benzovindiflupyr against Colletotrichum species. The broad‐spectrum efficacy of benzovindiflupyr within the Colletotrichum genus might be exploited when designing disease management strategies against various pathogens on a wide range of crops. Other mechanism(s) than fungicide target‐site modification may be responsible for differential sensitivity of Colletotrichum species to SDHI fungicides. © 2016 Society of Chemical Industry